Multimodal Evaluation of Neurovascular Functionality in Early Parkinson's Disease - Laganà, Maria Marcella; Pirastru, Alice; Pelizzari, Laura; Rossetto, Federica; Di Tella, Sonia; Bergsland, Niels; Nemni, Raffaello; Meloni, Mario; Baglio, Francesca (Frontiers in Neurology, 2020)
Parkinson's disease (PD) is a multi-system neurological condition affecting different neurotransmitter pathways characterized by aberrant functional connectivity (FC) and perfusion alteration. Since the FC, measuring neuronal activity, and cerebral blood flow (CBF) are closely related through the neurovascular coupling (NVC) mechanism, we aimed to assess whether FC changes found in PD mirror perfusion ones. A multimodal MRI study was implemented by acquiring resting state functional MRI (rsfMRI) and arterial spin labeling (ASL) datasets on a group of 26 early PD (66.8±8 years, 22 males, median [interquartile range] Hoehn & Yahr=1.5 [1]) and 18 age and sex-matched healthy controls (HCs). In addition, a T1-weighted MPRAGE was also acquired in the same scan session. After a standard preprocessing, resting state networks (RSNs) and CBF maps were extracted from rsfMRI and ASL dataset respectively. Then, by means of dual regression algorithm, performed on RSNs, cluster of FC differences between groups were obtained and used to mask CBF maps in the subsequent voxel-wise group comparison. Furthermore, a gray matter (GM) volumetric assessment was performed, within FC cluster, in order to exclude tissue atrophy as a source of functional changes. Reduced FC for PD patient with respect to HC group was found within sensory-motor network (SMN, pFWE=0.01) and visual networks (VNs, primary pFWE=0.022 and lateral pFWE=0.01). The latter was accompanied by a decreased CBF (primary pFWE=0.037, lateral pFWE=0.014 VNs), while no GM atrophy was detected instead. The FC alteration found in the SMN of PD might be likely due to a dopaminergic denervation of the striatal pathways causing a functional disconnection. On the other hand, the changes in connectivity depicted in VNs might be related to altered non-dopaminergic system, since perfusion was also reduced, revealing a compromised NVC. Finally, the absence of GM volume loss might imply that functional changes may potentially anticipate neurodegeneration. In this framework, FC and CBF might be proposed as early functional biomarkers providing meaningful insights in evaluating both disease progression and therapeutic/rehabilitation treatment outcome.